The current literature regarding the cardiovascular effects of electronic cigarettes. (March 2016) - Nelluri, Bhargava; Murphy, Katie; Mookadam, Farouk; Mookadam, Martina
Smoking is the leading cause of preventable morbidity and mortality globally. Electronic cigarettes are marketed both as nicotine substitutes and recreational devices. The popularity of electronic cigarettes has superseded other forms of nicotine replacement therapy. They are also popular in 'never smokers'. This review summarizes the available data regarding the cardiovascular effects of electronic cigarettes. The existing literature is limited and short term with a lack of high-quality studies and adequate follow-up. The available literature suggests that electronic cigarettes have sympathomimetic effects related to nicotine exposure, however, electronic cigarettes also contain other chemicals that require further investigation. Sparse data suggest vascular injury may be another concern. Further research is needed before broad recommendations can be made.